Phytocannabinoids - An Overview of the Analytical Methodologies for Detection and Quantification of Therapeutically and Recreationally Relevant Cannabis Compounds. (2nd January 2023) - Madden, Olena; Walshe, Jessica; Kishore Patnala, Prem; Barron, John; Meaney, Claire; Murray, Patrick
Abstract: The legalization of the cultivation of low Δ9-tetrahydrocannabinol (Δ9-THC) and high cannabidiol (CBD) Cannabis Sativa plants is gaining momentum around the world due to increasing demand for CBD-containing products. In many countries where CBD oils, extracts and CBD-infused foods and beverages are being sold in health shops and supermarkets, appropriate testing of these products is a legal requirement. Normally this involves determining the total Δ9-THC and CBD and their precursor tetrahydrocannabinolic acids (THCA) and cannabidiolic acid (CBDA). As our knowledge of the other relevant cannabinoids expands, it is likely so too will the demand for them as additives in many consumer products ensuring a necessity for quantification methods and protocols for their identification. This paper discusses therapeutically relevant cannabinoids found in Cannabis plant, the applicability and efficiency of existing extraction and analytical techniques as well as the legal requirements for these analyses. Graphical Abstract: UF0001